PENGARUH TEKANAN AKADEMIK TERHADAP PRESTASI AKADEMIK MAHASISWA PENDIDIKAN EKONOMI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET - Sakinatur Rahmawati; Mintasih Indriayu; Muhammad Sabandi (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
This study targeted to discover the relationship of academic pressure on academic achievement Economic Education student of Teacher Training and Education Faculty Sebelas Maret University. This research used quantitative descriptive method. A total of 131 college students randomly selected from all collage students in Economic Education Faculty of Teaching Training and Education Faculty Sebelas Maret University participated in this study. The sampling technique used is a stratified proportional random sampling. Data collection used questionnaire method and documentation. Data analysis technique used is simple regression analysis. The result showed that academic pressure has a significant influence on academic achievement. While the coefficient of determination of 0.125. That means 12.5% of academic achievement was influenced by academic pressure.